Indicadores de desempenho de projetos: a relação com o posicionamento estratégico e a natureza dos projetos no varejo brasileiro - Bitencourt, Lorene Carvalho (2014)
Retailing is an important segment in the Brazilian market and this is quite a market pressured by delivering short-term results despite the forces for creating and sustaining competitive advantage. Investments in projects glimpses for results aligned with the expectations from the business. And especially, they need to be aligned to strategic positioning and also become part of its achievement. The main objective of this study was to identify how the performance indicators of projects relate to the strategic positioning and nature of the project in the retail sector. Accordingly to this research question was: "How the indicators of project performance relate to the strategic positioning and nature of the project in the retail sector?. To answer it was identified in the theoretical review some propositions that have been investigated by means of an exploratory single case study, qualitative approach and broad inductive method in a large Brazilian retail in which it was used. In addition to the propositions were used, the Delta Model (Hax & Wilde II , 2001) and the Model of the Five Dimensions of Successful Projects (Shenhar & Dvir , 2010) as axes of the interview. The performance indicators of projects are directly influenced by the strategic positioning and the nature of the project. One highlight is the identification of the strategic positioning of the retailer is facing as this Best Product positioning is not expected by the literature. It was found that the alignment and balancing of the dimensions of indicators is an essential aspect for the success of strategic positioning . The results showed influences, especially the nature of the project. Moreover, since each project aims to achieve a certain goal, proved necessary to have the alignment and balancing of the dimensions of indicators for the organization for successful strategic positioning.